2021
DOI: 10.1038/s41598-021-93772-x
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral versus suprapubic catheterization to test urethral function in rats

Abstract: Transurethral and suprapubic catheterization have both been used to test urethral function in rats; however, it is unknown whether these methods affect urethral function or if the order of catheterization affects the results. The aim of this cross-over designed experiment was to compare the effects of catheterization methods and order on leak point pressure (LPP) testing. LPP and simultaneous external urethral sphincter electromyography (EUS EMG) were recorded in anesthetized female virgin Sprague-Dawley rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(55 reference statements)
0
2
0
1
Order By: Relevance
“…The concern regarding transurethral catheters is that it can affect urethral function and increase leak point pressure (LPP). However, several studies have demonstrated that the use of catheterization does not alter urethral function [22][23][24]. The ICCS Standardization Report on Urodynamic Studies of the Lower Urinary Tract in Children recommends the use of either methods; however, risks should be weighed against benefit when the suprapubic route is used.…”
Section: Discussionmentioning
confidence: 99%
“…The concern regarding transurethral catheters is that it can affect urethral function and increase leak point pressure (LPP). However, several studies have demonstrated that the use of catheterization does not alter urethral function [22][23][24]. The ICCS Standardization Report on Urodynamic Studies of the Lower Urinary Tract in Children recommends the use of either methods; however, risks should be weighed against benefit when the suprapubic route is used.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while some mouse cystometric studies have estimated the flow rate during voiding [ 181 , 211 ], the current assessment of urine flow in mice commonly depends on the observation of urine output and increased bladder pressure, thereby hindering the ability to distinguish coordinated voiding from non-voiding urine flow (i.e., involuntary urine expulsion associated with detrusor overactivity). Although transurethral catheterization does not appear to affect urethral function, as assessed during rodent CMG [ 212 ], small PE-50 catheters are prone to blockage [ 212 ]. In addition, longitudinal assessment is more challenging with the chronic catheter and electrode implantation commonly performed in small animals (e.g., inflammation, urinary tract infection, stone formation, bleeding, and catheter blockade) [ 158 , 171 ] compared to transurethral approaches.…”
Section: Considerations For the Application Of Animal Models In Nlutd...mentioning
confidence: 99%
“…Ургентная инконтиненция составляет 22-36%, смешанная -29%, на долю других типов приходится от 5% до 10%. Стандартные методы лечения часто обеспечивают симптоматическое облегчение, но не нацелены на основную этиологию и демонстрируют огромную вариабельность результатов от пациента к пациенту, ограниченный успех и осложнения, связанные с процедурами [1,2].…”
unclassified